PENGEMBANGAN LKS BERBASIS ICT PADA MATERI SISTEM SYARAF UNTUK SISWA KELAS XI RSBI - ADE INTAN PERMATA A (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Functionally, nervous system is an abstract material; therefore, for learning this material it requires worksheet completed with media. This study combined worksheet with animation and web media. The purpose of this  research was to determine the feasibility of ICT-based student worksheets based on of 2 biology lecturers’ and 2 biology teachers’ review. Based on the biology lecturer’s and teacher’s review, each component of this ICT-based student worksheet of nervous system is feasible enough even very feasible. Although this worksheet had been examined by some lecturers and teachers, actually it still need some more revisions. Key words:  development research, ICT-based student worksheet, nervous system